Evaluation of the impact of ground-level concentrations of SO2, NOx, CO, and PM10 emitted from a steel melting plant on Muscat, Oman. (April 2018) - Abdul-Wahab, Sabah; Fadlallah, Sulaiman; Al-Rashdi, Moosa
Abstract: Steel melting plants expel multiple pollutant gasses and particles and, as a result, they impact the surrounding air quality. The main objective of the current study was to investigate the concentration dispersion of sulfur dioxide (SO2 ), carbon monoxide (CO), nitrogen oxides (NOx ) and particulate matter with an aerodynamic diameter of less than 10 μm (PM10 ) emitted from a steel plant located in Muscat, Oman. This investigation was supported by the use of CALPUFF dispersion modeling software. The study analysis was based on selected modeling days that represent two different periods of the year: winter and summer. CALPUFF case study simulation results showed that winter NOx concentration levels exceeded the allowable concentrations set by the United States Environmental Protection Agency (U.S. EPA) standards. On the other hand, SO2, CO, and PM10 simulated results were within the allowable concentration limits.